Predicting major bleeding in patients with noncardioembolic stroke on antiplatelets - Hilkens, Nina A.; Algra, Ale; Diener, Hans-Christoph; Reitsma, Johannes B.; Bath, Philip M.; Csiba, Laszlo; Hacke, Werner; Kappelle, L. Jaap; Koudstaal, Peter J.; Leys, Didier; Mas, Jean-Louis; Sacco, Ralph L.; et al. (American Academy of Neurology, 2017)
Objective: To develop and externally validate a prediction model for major bleeding in patients with a TIA or ischemic stroke on antiplatelet agents.